PELATIHAN BUDIDAYA IKAN HIAS DAN CARA PEMASARANNYA DI MEDIA SOSIAL UNTUK MENAMBAH PENDAPATAN - Hafiz Santak Taram; Rafika Rahmawati; Siti Mardiah (LPPM Universitas Islam 45, 2022)
The Covid-19 era had a big impact, especially for the lower middle class, because the economy was declining and there were also many reductions in the number of employees in various companies. So that there is a need for innovation to open your own business, one of the easy and inexpensive businesses is ornamental fish cultivation. The research method used in the study was training for ornamental fish cultivation with the result of increasing the knowledge and understanding of residents about the cultivation and marketing of betta type ornamental fish as a business opportunity to increase income during the Covid-19 pandemic.